It takes two to tango: Spousal risk preferences and CEO risk-taking behavior - Antoniou, Constantinos; Cuculiza, Carina; Kumar, Alok; Yang, Lizhengbo (Journal of Corporate Finance, 2024)
Using hand-collected data on the cultural origins of S&P 500 CEOs and their spouses, we examine whether differences in risk attitudes within marriages influence corporate risk-taking behavior. We find that CEOs with more risk averse spouses adopt relatively safer corporate policies. The effect is stronger if the CEO comes from a more collectivist culture , has been married more recently, or shares more responsibilities with their spouse. Together, these findings suggest that the cultural composition of CEOs’ households and their spouses’ risk preference affect corporate risk-taking behavior.